Physical exercise and major depressive disorder – where do we stand? - Mota-Pereira, Jorge (2012)
Depression is the most common mental disorder, affecting a large population worldwide. Of the psychiatric syndromes which present mood disorders, major depressive disorder (MDD) is one of the most severe due to the long periods of depressed mood, somatic symptoms, cognitive disturbances, clinically significant distress and impairment in everyday functioning. The causes of MDD are complex and associated with environmental and biological aspects. Treatment comprises structured forms of psychotherapy and antidepressant medication but remission rates are low and justify the implementation of an alternative effective treatment. Various authors have associated physical exercise with the treatment of depression and different biological and psychological hypotheses have been proposed. Several clinical trials have been performed and, while some authors report no apparent association, the majority of the published data demonstrates a positive effect of physical exercise on both depressive symptoms and Quality of Life (QoL). In this review, the current status of exercise associated treatment of MDD is addressed, relevant data and models are discussed, and an updated view of the current situation is presented.